Interference graph based adaptive interference coordination method in indoor UDN - Xuanli WU; Ziyi XIE; Wei WU (Tongxin xuebao)
An interference graph based adaptive interference coordination method was proposed for indoor scenario of ultra dense network (UDN).The algorithm aimed at maximizing system throughput.Firstly,the interference relationship in the system was modeled as an interference graph,and the iterative coloring algorithm was used to determine the available resources of each small cell base station (SBS).Thereafter,the SBS allocated resources to each user by using a throughput optimizing resource allocation algorithm.The method could adaptively select a resource allocation strategy according to the network topology and channel conditions,thereby mitigating interference in the system.The simulation results show that compared with the existing methods,the proposed method effectively reduces the system outage probability while significantly improving the throughput performance through a small additional signaling overhead.